Oncolytic HSV Therapy Modulates Vesicular Trafficking Inducing Cisplatin Sensitivity and Antitumor Immunity - Hong, Bangxing; Chapa, Valerie; Saini, Uksha; Modgil, Puneet; Cohn, David E.; He, Guangan; Siddik, Zahid H.; Sood, Anil K.; Yan, Yuanqing; Selvendiran, Karuppaiyah; Pei, Guangsheng; Zhao, Zhongming; et al. (Clinical cancer research, 2021)
Here we investigated the impact of oncolytic herpes simplex virus (HSV) treatment on cisplatin sensitivity of platinum-resistant ovarian cancer, and the impact of the combination on immunotherapy. Therapeutic efficacy of the combination was assessed in platinum-resistant human and murine ovarian cancer peritoneal metastatic mouse models ( = 9-10/group). RNA sequencing along with flow cytometry of splenocytes from treated mice was employed to examine the effect of antitumor immune response ( = 3/group). Anti-PD-1 antibody was performed to evaluate impact on checkpoint inhibition . Gene Ontology pathway analysis uncovered disruption of cellular extracellular vesicle (EV)-related pathways in infected cells (FDR = 2.97E-57). Mechanistically, we identified reduced expression of transporters expressed on EV implicated in cisplatin efflux. The increased cisplatin retention led to increased cisplatin-DNA adducts, which resulted in micronuclei and the subsequent activation of cGAS-STING pathway with a significant activation of innate immune cells and translated to an increase in antitumor immunity and efficacy. In mice bearing platinum-resistant ovarian cancer, we also observed a feedback induction of PD-L1 on tumor cells, which sensitized combination-treated mice to anti-PD-1 immune checkpoint therapy. To our knowledge, this is the first report to show HSV-induced cisplatin retention in infected cells. The consequential increased damaged DNA was then expelled from cells as micronuclei which resulted in induction of inflammatory responses and education of antitumor immunity. The combination therapy also created an environment that sensitized tumors to immune checkpoint therapy.